Aortic dilation and growth in women with Turner syndrome. Issue 2 (15th June 2022) - Meccanici, Frederike; Schotte, Mathilda H; Snoeren, Miranda; Bons, Lidia R; van den Hoven, Allard T; Kardys, Isabella; Budde, Ricardo P J; van den Bosch, Annemien E; Duijnhouwer, Anthonie L; Roos-Hesselink, Jolien W
Abstract : Objective: Women with Turner syndrome (TS) are at increased risk of aortic dissection, which is a life-threatening event associated with aortic dilation. Knowledge on the development of aortic dilation over time remains limited. This study aims to describe the prevalence of aortic dilation, to find associated factors and to study aortic growth in women with TS. Methods: In this prospective multicentre cohort study, consecutive adult women with genetically proven TS included between 2014 and 2016 underwent ECG-triggered multiphase CT angiography at baseline and after 3 years. Aortic diameters were measured at seven levels of the thoracic aorta using double oblique reconstruction and indexed for body surface area. Ascending aortic dilation was defined as an aortic size index >20 mm/m 2 . Aorta-related and cardiovascular events were collected. Statistical analysis included linear and logistic regression and linear mixed effects models. Results: The cohort consisted of 89 women with a median age of 34 years (IQR: 24–44). Ascending aortic dilation was found in 38.2% at baseline. At baseline, age (OR: 1.08 (95% CI 1.03 to 1.13), p<0.001), presence of bicuspid aortic valve (BAV) (OR: 7.09 (95% CI 2.22 to 25.9), p=0.002) and systolic blood pressure (OR: 1.06 (95% CI 1.02 to 1.11), p=0.004) were independently associated with ascending aortic dilation. During a median follow-up of 3.0 (2.4–3.6) years (n=77), significant aortic growth was found only at the sinotubular junction (0.20±1.92 mm, p=0.021). No aortic dissection occurred, one patient underwent aortic surgery and one woman died. Conclusions: In women with TS, ascending aortic dilation is common and associated with age, BAV and systolic blood pressure. Aortic diameters were stable during a 3-year follow-up, apart from a significant yet not clinically relevant increase at the sinotubular junction, which may suggest a more benign course of progression than previously reported.